Tourism to Pilgrimage Sites in Bangladesh: A Sustainability Framework - Azad, Md Abul Kalam (Curtin University, 2025)
Using three Mazar (Sufi tomb) sites in Bangladesh – of Lalon Fakir, Khan Jahan Ali and Shah Jalal, the study examines pilgrimage tourism. Adopting a mixed-methods approach with a survey and interviews, the analysis reveals that pilgrims are drawn to the sites in search of spirituality and interconnectedness with nature which also puts aside materialism and consumerism. The study also explains the significance of pilgrimage tourism as supporting local communities and cultures and contributing to their sustainability.